Lama Pengalaman Klinik Perawat Dengan Ketepatan Skoring Virulensi COVID-19 Menggunakan Aplikasi EWSS (Early Warning System Score) - Ardiyani, Vita Maryah; Sutriningsih, Ani (Care : Jurnal Ilmiah Ilmu Kesehatan, 2023)
Over time, the COVID-19 virus mutates and can spread rapidly, requiring more accurate treatment. Adequate treatment is essential for healing and reducing the spread of diseases. Moreover, nursing has become the main health workforce in controlling COVID-19. The study aims to test the relationship between nursing clinical experience and the accuracy of COVID-19 virulence scoring using the Early Warning System Score application. The study used a correlation analytic design with a cross sectional approach. The population used in this study was nurses who filled out questionnaires online in East Java. A sample of 311 respondents. The results showed a significant relationship between nursing clinical experience and accuracy of scoring virulence of COVID-19 using the Early Warning System Score application. Treatment of COVID-19 should remain in the evaluation, especially the provision of appropriate nursing care for patients with COVID-19 by nurses. Researchers can add clinical experience-supporting variables to find out the various compensators of nurses’ competence.